Nepal's foreign policy and emerging global trends - Shrestha, Mohan Krishna (ed.); Jaiswal, Pramod (ed.); Poudel, Mitra Bandhu (ed.) (New Delhi G.B. books, 2021)
This book consists different aspects of Nepalese foreign policy such as foreign aid competition, transboundary water issues, India-China geopolitical rivalry, the impact of China's Belt and Road Initiative, and the role of Nepal at the regional as well as multilateral organizations such as SAARC and the UN.
Keywords: Nepal's foreign policy